Family language policy retention across generations: childhood language policies, multilingualism experiences, and future language policies in multilingual emerging Canadian adults - Pagé, Leah L.; Noels, Kimberly A. (Frontiers in Psychology, 2024)
Introduction Language policies in multilingual families refer to parents’ decisions, whether explicitly articulated or not, regarding which languages will be used in which contexts. However, because most studies that explore language allocation focus on families with young children, they do not address how family language policies impact the retention of a home language through to the next generation. The present study investigates an important perspective on this issue, specifically how emerging adults’ childhood experiences with their family language policy relate to the languages they currently use and plan to retain in the future. Methods In all, 62 multilingual Canadian adults, aged between 17 and 29 years, participated in focus group interviews concerning their experience of language policies in their birth families, their current beliefs concerning language allocation and retention, and their plans about language policy in their future families. Results The data revealed that not only are most participants interested in retaining their home language, thereby continuing to speak the language in their future families, but most are also open to incorporating additional languages into their policies. Discussion The results provide insight into how to identify effective heritage language retention policies that transcend generations.